Submassive hepatic necrosis distinguishes HBV-associated acute on chronic liver failure from cirrhotic patients with acute decompensation - Li, Hai; Liebe, Roman; Singer, Manfred V.; Dooley, Steven; Ebert, Matthias; Weng, Honglei (Journal of hepatology, 2015)
Background & Aims: Distinguishing between acute on chronic liver failure (ACLF) and decompensated liver cirrhosis is difficult due to a lack of pathological evidence. Methods: A prospective single-center study investigated 174 patients undergoing liver transplantation due to acute decompensation of hepatitis B virus (HBV)-associated liver cirrhosis. Two groups were distinguished by the presence or absence of submassive hepatic necrosis (SMHN, defined as necrosis of 15-90% of the entire liver on explant). Core clinical features of ACLF were compared between these groups. Disease severity scoring systems were applied to describe liver function and organ failure. Serum cytokine profile assays, gene expression microarrays and immunohistochemical analyzes were used to study systemic and local inflammatory responses. Results: SMHN was identified in 69 of 174 patients proven to have cirrhosis by histological means. Characteristic features of SMHN were extensive necrosis along terminal hepatic veins and spanning multiple adjacent cirrhotic nodules accompanied by various degrees of liver progenitor cell-derived regeneration, cholestasis, and ductular bilirubinostasis. Patients with SMHN presented with more severely impaired hepatic function, a higher prevalence of multiple organ failure (as indicated by higher CLIF-SOFA and SOFA scores) and a shorter interval between acute decompensation and liver transplantation than those without SMHN (p<0.01 for all parameters). Further analyzes based on serum cytokine profile assays, gene expression microarrays and immunohistochemical analyzes revealed higher levels of anti-inflammatory cytokines in patients with SMHN. Conclusions: SMHN is a critical histological feature of HBV-associated ACLF. Identification of a characteristic pathological feature strongly supports that ACLF is a separate entity in end-stage liver disease.